Governing ASEAN e-commerce : getting cloudier - Pitakdumrongkit, Kaewkamol (2015)
Big business has tapped into ASEAN’s burgeoning e-commerce market and regional governments have enacted measures to govern the Internet “cloud”. However institutional gaps remain and a region-wide legislation for e-commerce is required.